Intra-specific variation in Nothofagus glauca, an endemic species of the Mediterranean forests of Chile - Santelices Moya, Rómulo; Vergara, Rodrigo; Cabrera Ariza, Antonio; Espinoza Meza, Sergio; Silva Flores, Patricia (BOSQUE, 2020)
In forest conservation, especially in a climate change scenario, to guide decision-making, it is essential to know the intra-specific variation of multiple traits that exist in a species. Therefore, the objective of this work was to analyze the current state of knowledge about the variation of Nothofagus glauca. In this way, guidelines may be proposed for future programs for the conservation of genetic resources or the restoration of forests of this species. Important intra-specific variability is analyzed and evidenced in aspects related to its spatial distribution, its variation in ecological distribution, its populations associated with the forest typology, its genecological differentiation, its variation in growth and its genetic variation detected by isoenzymatic and molecular markers. Based on the abundant research, a step to a second experimental phase is proposed to select populations capable of adapting to the new environmental conditions resulting from climate change, which must consider the microbiome of this species. It is proposed that, in this way, efficient conservation and restoration of N. glauca will be achieved.